An overview of migratory birds in Brazil - Somenzari, Marina (2018)
We reviewed the occurrences and distributional patterns of migratory species of birds in Brazil. A species was classified as migratory when at least part of its population performs cyclical, seasonal movements with high fidelity to its breeding grounds. Of the 1,919 species of birds recorded in Brazil, 198 (10.3%) are migratory. Of these, 127 (64%) were classified as Migratory and 71 (36%) as Partially Migratory. A few species (83; 4.3%) were classified as Vagrant and eight (0,4%) species could not be defined due to limited information available, or due to conflicting data.